Field Trip: Channel-Levee Facies and Sea Floor Fan Lobes in the Turbidites of Lower Kutei Basin, East Kalimantan - Irfan Cibaj (Ikatan Ahli Geologi Indonesia, 2011)
Recently open outcrops in the lower Kutei basin have been interpreted as slope turbidites. The new outcrops show channel-levee complexes. The sandstone bodies are mostly constituted by mass flows and debris flows which pinch out in short distance to thin bedded turbidites and silt shale alternations. This is interpreted as the transition from channel margin to levees. Channels are filled in general by thick mass flow deposits.A detailed geometry of sandstone reservoirs in slope turbidite channel – levee complexes is described. Precise measurements of different architectural elements of the complexes are carried out in field outcrops. Two outcrops will be the object of this paper. One of them shows sea floor lobe and the other shows channel levee complexes in a slope.